Protocol For Electronic Digital Signature of Asymmetric The Importance of Age Characteristics in Working with Primary School Students (Texas Journal of Multidisciplinary Studies, 2022)
In educational process there are several key factors critical to the efficiency of the lessons conducted. Among them it is important to take into account the age characteristics of junior school children. The following article is devoted to the physical and psychological qualities of elementary school children so that the teachers can identify appropriate approach for individual class members